EVALUASI KEBIJAKAN PROVINSI SUMATERA BARAT TENTANG PENDIRIAN BUMD PT. BALAIRUNG CITRAJAYA SUMBAR - Putra, Hadi; Koeswara, Hendri; Syamsurizaldi, Syamsurizaldi (Jurnal Politik Pemerintahan Dharma Praja, 2021)
One form of local government public policy is the establishment of Regional Owned Enterprises policy. The purpose of this study was to evaluate the policy of the establishment of a Regional Owned Enterprise PT. Balairung Citrajaya Sumbar. The theory used is the policy evaluation of Althaus et al. with indicators: Input, Process, Output, and Outcome. The research approach used is descriptive qualitative with data collection, document review, interviews and observations. The results showed that the establishment policy of PT. Balairung Citrajaya Sumbar has not been effective and inefficient based on; (1) Inputs, the basic material of the policy is that there is no feasibility study, human resources are adequate, financial resources have not yet received all capital participation from districts/cities in accordance with the cooperation agreement. (2) The process, the implementation of the policy has reached the target, namely the formation and operation of PT. Balairung Citrajaya Sumbar. Policy implementers have carried out their respective roles according to their respective functions. However, it has not been effective in achieving policy objectives and is inefficient in managing resources into outputs, (3) Output, the policy results have been received in the form of dividends, but the ratio is still very small compared to inputs and has not been received continuously every year. (4) Outcome, the formal objective of the policy to increase development is still not significant because of the small contribution to PAD. Another positive impact is that socially, the Balairung Hotel has become an icon and meeting point for the people of West Sumatra in Jakarta. Meanwhile, the negative impacts include the image of the West Sumatra Provincial Government not being able to manage BUMD properly and the increase in the APBD burden for renting the West Sumatra Provincial Liaison Agency office in Jakarta, as well as the reduced function of the Balairung as a shelter for Minang people in Jakarta.